Pemanfaatan Digital Marketing Bagi Masyarakat Tanjung Medan - Karim, Abdul; Kusmanto; Purba, Elvitrianim (Jurnal Mitra Pengabdian Farmasi, 2022)
Tanjung Medan Village is a village located in the District of West Blade, Labuhanbatu Regency, North Sumatra Province. Tanjung Medan village itself has a lot of agricultural commodities that are obtained, both palm oil, rubber, even rattan and many more incomes that can be obtained in this area. However, with conditions that are too far from urban access, the results obtained are not optimal but can only be used for daily needs. Thus, to overcome the problems faced by the people of Tanjung Medan, we are coaching the use of digital marketing for the people of Tanjung Medan Village, which aims to increase family income. The higher the income, the more prosperous the people are.